A Celebrity Endorsement Effect On Purchase Intention With Brand Image Mediation And Moderation Negative Publicity - Hamidah, Salwa; Ramadhani, Silvia Nur (Lentera Ilmu Nusantara, 2024)
The purpose of this study is to determine the description and influence of Celebrity Endorsement, Purchase Intention, variables mediated by Brand Image and moderated by Negative Publicity. The research method uses a quantitative method with descriptive analysis. The research sample was 100 respondents with a purposive sampling technique. The results showed that Brand Image had a positive and significant influence on Purchase Intention, Celebrity Endorsment had a positive and significant influence on Negative Publicity, Celebrity Endorsment had a positive and significant influence on Purchase Intention, and Negative Publicity had a positive and significant influence on Purchase Intention, but the Celebrity Endorsment variable moderated by Brand Image on Purchase Intention was not have no and insignificant effect on Purchase Intention and Celebrity Endorsment moderated by Negative Publicity on Purchase Intention has no effect and is not significant on Purchase Intention. The role of brand image as a mediator of the influence of celebrity endorsement on buying interest shows that local cosmetics entrepreneurs must be able to manage and provide strategies to ensure the sustainability of local cosmetic products. The goal is to attract attention or attraction to increase consumer buying interest.